2009
DOI: 10.4049/jimmunol.0803523
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of NK Cell Function by Human Granulocyte Arginase

Abstract: The arginine-hydrolyzing enzyme arginase is constitutively expressed by human polymorphonuclear granulocytes (PMN). Upon PMN cell death arginase is liberated and depletes arginine in the microenvironment. This amino acid depletion suppresses T cell proliferation and cytokine secretion and emerges as a key mechanism of immunosuppression during chronic inflammation and tumor growth. Here we show that PMN arginase also severely impairs key functions of primary human NK cells as well as IL-2-activated NK cells. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 50 publications
2
90
0
2
Order By: Relevance
“…A similar regulation of human NK cells by arginase released from granulocytes has also been reported [31]. Furthermore, it has recently been shown that meschymal stromal cells transform neutrophils into an immunosuppressive phenotype in part by inducing arginase expression and activity [32,33].…”
Section: Discussionmentioning
confidence: 67%
“…A similar regulation of human NK cells by arginase released from granulocytes has also been reported [31]. Furthermore, it has recently been shown that meschymal stromal cells transform neutrophils into an immunosuppressive phenotype in part by inducing arginase expression and activity [32,33].…”
Section: Discussionmentioning
confidence: 67%
“…Накопичені дані свідчать про те, що існують дві грані nO: вона може діяти і як промотор пухлини, і як інгібітор пухлинних клітин [17]. Подвійна роль nO в розвитку раку залежить від його концентрації та інших супутніх чинни ків.…”
Section: аргінінunclassified
“…Метаболическое действие ней-ротоксичности аммиака связано с изменением уровня секреции ROS и RNS, метаболизма NO, уровня cAMP, MAPK-киназного сигнального пути, структуры цитоскелета. Токсическое дей-ствие NH 3 на клетки приводит к усилению про-дукции TNFα и IL-1β, которые в свою очередь индуцируют продукцию ROS, активацию PKA, ERK и NF-κB [8,75]. Нельзя исключать, что NH 3, генерируемый в результате активности АД, будет оказывать схожее токсическое действие на дру-гие типы клеток.…”
Section: иммуносупрессорные эффекты аргининдеиминазыunclassified